Influence of bottom ash from coal fire boiler in cement brick toward mechanical properties - Zulhusni, Razaob (2010)
Recycling is the act of processing the used material for use in creating new product. The usage of natural aggregate is getting more and more intense with the advanced development in infrastructure area. in order to reduce the usage of natural aggregate, recycled aggregate can be used as a replacement materials. In Malaysia the used of bottom ash from coal fire boiler power plant become one of the serious environmental problems facing now. Therefore, new alternative needed to recycle and reuse them to avoid those problem from become more serious environmental problem. Several researches have been developed for its reuse and it was found that the use of disposal bottom ash in the cement brick is a possible form Of its to improve certain of properties of cement brick, such as better compression performance, ductility, and lightweight. in this study "Bottom Ash" were use to determine the mechanical characteristics of recycled aggregate concrete. Test that has been done with different replacement percentage of "Bottom Ash" based on weight of the fine aggregate (0%, 25%, 50% and 100%). At the end of the study, it can observe that the replacement of "Bottom Ash" reduce the performance of cement brick in side of strength, but it produces more ductile and lightweight concrete with high workability of mixture which is suitable for application of structures that are more resistant to high impact and able to sustain failure mode longer compared to the ordinary concrete.